Carbon dioxide rebreathing caused by deformed silicon leaflet in the expiratory unidirectional valve - Arumugam Vasudevan; Satyen Parida; Lenin Babu Elakkumanan; Sandeep Mishra (Wolters Kluwer Medknow Publications, 2013)
Rebreathing of carbon dioxide caused by incompetent 'cage and disc' unidirectional valves has been reported earlier. Some manufacturers have changed the design of unidirectional valves to 'flexible leaflets'. We report a series of cases where a deformed membrane leaflet in expiratory unidirectional valves led to rebreathing of carbon dioxide.